Long-Term Outcomes of MUA for Stiffness in Primary TKA - Pivec, Robert; Issa, Kimona; Kester, Mark; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2013)
Knee stiffness following primary total knee arthroplasty (TKA) is a well-recognized problem which leads to poor patient outcomes and may limit patient activities of daily living. Manipulation under anesthesia (MUA) is one option for the treatment of knee stiffness. However, there has been controversy regarding the safety and long-term efficacy of this procedure. A systematic review of the literature was performed to identify studies that reported the clinical outcomes and measured range of motion for patients undergoing MUA. Fourteen studies (913 patients) reported range of motion results following MUA at up to 10-year follow-up. The mean premanipulation and final range of motion were 66 and 99 degrees, respectively. Compared with preoperative range of motion, the gain in the range-of-motion arc at 1-, 5-, and 10-year follow-up was 30, 33, and 33 degrees, respectively. Complications were rare with only two reported periprosthetic fractures, resulting in an incidence of 0.2%. MUA for a stiff primary TKA is an efficacious procedure to restore range of motion. Early gains in motion appear to be maintained at long term, and in some cases patients may gradually improve further at mid-term follow-up. The risk of periprosthetic fracture is low, making MUA a safe option for improving knee range of motion.
Keywords: knee stiffness; manipulation under anesthesia (MUA); TKA